Organic-inorganic hybrid {Zr6Sn4} type crystalline tin zirconium oxygen cluster patterned material as well as preparation method and application thereof

By introducing butyltin and halogen carboxylic acid ligands into zirconium oxygen clusters, the structure of tin zirconium clusters is solved, and the problems of insufficient response and etch resistance of traditional photoresist in extreme ultraviolet lithography technology are achieved, achieving high Resolution and high-quality film forming properties are suitable for lithography applications in next-generation technology nodes.

CN119241583APending Publication Date: 2025-01-03FUJIAN INST OF RES ON THE STRUCTURE OF MATTER CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411202770.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-29
Publication Date
2025-01-03

AI Technical Summary

Technical Problem

Traditional chemical amplification photoresist is poorly responded and has insufficient etch resistance in extreme ultraviolet (EUV) lithography technology. The existing metal oxygen cluster materials have limitations in nanoscale dimensions and structural uniformity, making it difficult to meet the next generation of technologies. Node requirements.

Method used

Introduce butyltin (Sn-C) bonds and halogen carboxylic acid ligands into zirconium oxygen clusters to enrich the structural type of tin zirconium clusters, regulate their solubility, film formation and photolithography properties, and form precise structural information. , high solution stability and high-quality film-forming properties of crystalline zirconium tin oxygen cluster materials.

Benefits of technology

Achieve high resolution, improve line edge roughness and improve lithography performance, providing new extreme UV photoresist technical insights suitable for advanced integrated circuit applications with resolutions up to 100nm or even 50nm.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119241583A_ABST
    Figure CN119241583A_ABST
Patent Text Reader

Abstract

The invention provides an organic-inorganic hybrid {Zr6Sn4} type crystalline tin zirconium oxygen cluster patterned material as shown in a formula (I) and a preparation method and application thereof, the patterned material has an octahedral [Zr6O8] construction unit, the construction unit is connected with four butyltin through bridging ligands, and the bridging ligands are bridged to form an organic-inorganic hybrid {Zr6Sn4} type crystalline tin zirconium oxygen cluster patterned material, and the bridging ligands are bridged to form an organic-inorganic hybrid {Zr6Sn4} type crystalline tin zirconium oxygen cluster patterned material. And halogen groups and carboxylic acid ligands are added as end-group ligands. The resolution ratio of a pattern formed after the patterning material provided by the invention is exposed and developed can reach 50nm. The patterned material provided by the invention contains adjustable bridging ligands, different radiation responsive metals and end group ligands. By introducing a functional group into the ligand, the variety and proportion of different metals can be adjusted, and the variety and number of the end group ligand can be regulated, so that the solubility, film-forming property, light absorption capacity and light sensitivity are further enhanced, the line edge roughness is improved, the resolution is improved, and the photoetching performance of the patterned material is regulated. Formula (I): (RSn) 4Zr6X2 (mu-O) 8 (mu-R 'O) 8 (L) 10.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of photoresist materials, and in particular relates to an organic-inorganic hybrid {Zr6Sn4} type crystalline tin zirconium oxide cluster patterning material and a preparation method and application thereof. Background Art

[0002] Extreme ultraviolet (EUV) nanolithography is critical to advancing the development of next-generation technology nodes. Conventional chemically amplified photoresists are approaching their application limits due to their poor response to EUV light and low etching resistance. In contrast, metal-containing photoresists, especially metal oxide clusters (MOCs), have become strong candidates to address this challenge due to their nanoscale size, well-defined structure and high EUV absorption ability. The comprehensive performance of photoresists is evaluated by RLS indicators, including resolution, line edge roughness and sensitivity. Generally, nanoscale photoresists with uniform size distribution help to improve resolution and improve line edge roughness. In addition, strong EUV absorption and high sensitivity determine its potential for commercial application.

[0003] Among various MOCs-based EUV photoresists, zirconium oxide clusters have been verified as efficient negative-tone photoresists, among which Zr6O4(OH)4L 12 It provides an ideal platform to explore the relationship between structure and lithographic performance. Zr6O4(OH)4L 12 It was selected as a model compound and attracted wide attention. Researchers have made many attempts to introduce mixed ligands, fluorine-containing ligands and additives into Zr6MAA to further improve its EUV lithography performance. This proves that zirconium-based metal oxide clusters have potential application prospects in patterning.

[0004] The exploration of EUV photoresists is not limited to zirconium oxo cluster nanomaterials, but also covers tin, indium, zinc and hafnium oxo clusters. Among these materials, organotin oxo clusters show excellent potential in lithography and have made significant contributions to advanced integrated circuit applications. The interaction between radiation and organotin oxo clusters and their solubility conversion behavior under EUV exposure have been studied experimentally and theoretically. Previous work proposed the following lithographic mechanism: radiation-induced homolysis of butyltin (Sn-C) bonds to generate alkyl radicals, which initiate cross-linking reactions, leading to the aggregation of nanoclusters, making them insoluble in the developer, thereby achieving negative lithography. In addition, tin has strong absorption of EUV light, with an absorption cross section of 1.095×10 7 cm 2 / mol, which is more than 20 times that of zirconium. Therefore, introducing Sn-C bonds into Zr6 oxygen clusters can significantly improve their lithographic performance by exploiting these established mechanisms and strong EUV absorption capabilities, providing new insights and progress in EUV photoresist technology. Summary of the invention

[0005] The present invention introduces butyltin (Sn-C) and halogen carboxylic acid ligands into zirconium-oxygen clusters, enriches the structural types of tin-zirconium clusters, and regulates the solubility, film-forming property and photolithographic performance of the tin-zirconium-oxygen clusters.

[0006] The crystalline zirconium tin oxide cluster provided by the present invention has the characteristics of accurate structural information, high solution stability, high-quality film-forming property, etc. Moreover, the raw materials are simple and easy to obtain, the crystal material synthesis method is simple, the yield is high, and it can be prepared in large quantities, and it is a very potential candidate photoresist material.

[0007] The present invention provides a patterned material, the molecular formula of which is shown in formula (I):

[0008] (RSn)4Zr6X2(μ-O)8(μ-R'O)8(L) 10

[0009] Formula (I);

[0010] Wherein, R is selected from H, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl or C 6-20 Aryl;

[0011] R' is selected from H, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl or C 6-20 Aryl;

[0012] X contains the same or different ligands, which are independently selected from ligands that can coordinate with Zr and Sn;

[0013] L contains the same or different ligands, which are independently selected from ligands capable of coordinating with Zr and Sn.

[0014] According to an embodiment of the present invention, R is selected from H, C 1-10 Alkyl, C 2-10 Alkenyl, C 2-10 Alkynyl or C 6-10 Aryl.

[0015] According to an embodiment of the present invention, R is selected from H, C 1-6 Alkyl, C 2-6 Alkenyl, C 2-6 Alkynyl or C 6-10 Aryl.

[0016] According to an embodiment of the present invention, R is selected from H, C 1-4 Alkyl, C 2-4 Alkenyl, C 2-4 Alkynyl or C 6-10Aryl.

[0017] According to an embodiment of the present invention, R is selected from H, methyl, ethyl, propyl, n-butyl, vinyl, methylpropenyl, propenyl, butenyl, ethynyl, propynyl, butynyl, phenyl, naphthyl, and the like.

[0018] According to an embodiment of the present invention, R' is selected from H, C 1-10 Alkyl, C 2-10 Alkenyl, C 2-10 Alkynyl or C 6-10 Aryl.

[0019] According to an embodiment of the present invention, R' is selected from H, C 1-6 Alkyl, C 2-6 Alkenyl, C 2-6 Alkynyl or C 6-10 Aryl.

[0020] According to an embodiment of the present invention, R' is selected from H, C 1-4 Alkyl, C 2-4 Alkenyl, C 2-4 Alkynyl or C 6-10 Aryl.

[0021] According to an embodiment of the present invention, R' is selected from H, methyl, ethyl, propyl, butyl, vinyl, methacryl, propenyl, butenyl, ethynyl, propynyl, butynyl, phenyl, naphthyl, and the like.

[0022] According to an embodiment of the present invention, X comprises identical or different ligands, independently selected from ligands containing but not limited to C, O, S, Se, Te, N, P, As, Sb, Cl, Br, I, etc. as coordinating atoms.

[0023] According to an embodiment of the present invention, X is the same or different ligands, independently selected from halogens, alkanes (C 1-20 Alkyl), aromatic hydrocarbons (C 6-20 Aromatic hydrocarbons), olefins (C 2-20 alkenyl), alkynes (C 2-20 ligands such as alkynyl), carboxylic acids, alcohols, thiols, phenols, sulfonic acids, phosphoric / phosphonic acids, phosphines, arsenic acids, nitriles, alcoholamines, pyridines, pyrazoles, imidazoles, piperazines, pyrazines, H2O, SO4, NO3 or the above ions.

[0024] According to an embodiment of the present invention, X comprises the same or different ligands, and the different ligands may be present in any ratio.

[0025] According to an embodiment of the present invention, L comprises identical or different ligands, independently selected from ligands containing but not limited to C, O, S, Se, Te, N, P, As, Sb, Cl, Br, I, etc. as coordinating atoms.

[0026] According to an embodiment of the present invention, L comprises the same or different ligands, independently selected from halogens, alkanes (C 1-20 Alkyl), aromatic hydrocarbons (C 6-20 Aromatic hydrocarbons), olefins (C 2-20 alkenyl), alkynes (C 2-20 alkynyl), carboxylic acids (for example, carboxylic acids or their derivatives, such as benzoate, o-methylbenzoate, m-methylbenzoate, 5-chloro-thiophene-2-carboxylate, p-chlorobenzoate, p-fluorobenzoate or trifluoromethylbenzoate), alcohols, thiols, phenols, sulfonic acids, phosphoric / phosphonic acids, phosphines, arsenic acids, nitriles, alcoholamines, pyridines, pyrazoles, imidazoles, piperazines, pyrazines, H2O, SO4, NO3 or ligands such as the above ions.

[0027] According to an embodiment of the present invention, L comprises the same or different ligands, and the different ligands may be present in any ratio.

[0028] According to an embodiment of the present invention, part or all of the Zr and Sn ions can be replaced by other elements, such as radiation-sensitive elements. Preferably, the radiation-sensitive elements are selected from any one or a combination of Na, Mg, Al, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Rb, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, Cs, Ba, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Hf, Ta, W, Re, Os, Ir, Pt, Au, Hg, Pb, Bi, and Po.

[0029] According to the embodiment of the present invention, functional groups may be further introduced into R, R', X, and L. The introduction of functional groups may adjust the light absorption ability, solubility, film-forming properties and other properties of the patterned material, thereby affecting the film thickness, film roughness, resolution, film adhesion and corrosion resistance.

[0030] According to an embodiment of the present invention, a radiation-sensitive functional group may be further introduced into R, R', X, and L. The introduction of the radiation-sensitive functional group may enhance the photosensitivity of the patterned material, improve the line edge roughness, and improve the resolution. The radiation-sensitive functional group may be, for example, a double bond, a triple bond, propylene oxide, or a compound of a combination thereof.

[0031] According to the embodiments of the present invention, the ratio of the coordinating atoms of the ligands to the metal ions in the patterning material of the present invention can be adjusted to improve its sensitivity, line edge roughness and resolution.

[0032] According to an embodiment of the present invention, the patterned material of the present invention has an octahedral [Zr6O8] building unit, which is connected to four butyltin groups through a cross-linked ligand, and is formed by adding a halogen group and a carboxylic acid group ligand as a terminal ligand. The cross-linked ligand is a carboxylic acid ligand and an alkoxy ligand.

[0033] According to an embodiment of the present invention, the patterning material is selected from the following compounds 1 to 7:

[0034] Compound 1: n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA) 10 ;

[0035] Compound 2: n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-oCH3) 10 ;

[0036] Compound 3: n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCH3) 10 ;

[0037] Compound 4: n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(TA-Cl) 10 ;

[0038] Compound 5: n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pCl) 10 ;

[0039] Compound 6: n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pF) 10 ;

[0040] Compound 7: n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCF3) 10 ;

[0041] Among them, BA represents benzoate, with the molecular formula of C7H5O2; BA-oCH3 represents o-methylbenzoate, with the molecular formula of C8H7O2; BA-mCH3 represents m-methylbenzoate, with the molecular formula of C8H7O2; TA-Cl represents 5-chloro-thiophene-2-carboxylate, with the molecular formula of C5H2O2SCl; BA-pCl represents p-chlorobenzoate, with the molecular formula of C7H4O2Cl; BA-pF represents p-fluorobenzoate, with the molecular formula of C7H4O2F; BA-mCF3 represents m-trifluoromethylbenzoate, with the molecular formula of C8H4O2F3. Among them, benzoate refers to the structure obtained by removing H from COOH of benzoic acid. Similarly, other roots have the same meaning.

[0042] According to an embodiment of the present invention, the crystal parameters of compound 1 are: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is c is α is 73.9040(10)°, β is 85.4470(10)°, γ is 68.1800(10)°, and V is

[0043] According to an embodiment of the present invention, the crystal parameters of compound 2 are: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is c is α is 97.3350(10)°, β is 90.0890(10)°, γ is 110.0550(10)°, and V is

[0044] According to the embodiment of the present invention, the crystal parameters of compound 3 are: the crystal system is monoclinic, the space group is C2 / c, and the unit cell parameter a is b is c is α is 90°, β is 96.103(4)°, γ is 90°, and V is

[0045] According to an embodiment of the present invention, the crystal parameters of compound 4 are: the crystal system is monoclinic, the space group is I2 / a, and the unit cell parameter a is b is c is α is 90.0°, β is 104.977(2)°, γ is 90.0°, and V is

[0046] According to an embodiment of the present invention, the crystal parameters of compound 5 are: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is c is α is 75.081(2)°, β is 72.591(2)°, γ is 85.302(2)°, and V is

[0047] According to an embodiment of the present invention, the crystal parameters of compound 6 are: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is c is α is 77.8622(12)°, β is 74.8997(17)°, γ is 86.2910(18)°, and V is

[0048] According to the embodiment of the present invention, the crystal parameters of compound 7 are: the crystal system is monoclinic, the space group is C2 / c, and the unit cell parameter a is b is c is α is 90°, β is 93.136(2)°, γ is 90°, and V is

[0049] The present invention also provides a method for preparing the above-mentioned patterned material, comprising the following steps:

[0050] The material can be prepared by a solvothermal synthesis method using a tin source, a zirconium source, a ligand and a solvent;

[0051] According to an embodiment of the present invention, the tin source is selected from any one of the following: butyl stannoic acid, dibutyl tin chloride, dibutyl stannoic acid, phenyl tin chloride and the like.

[0052] According to an embodiment of the present invention, the zirconium source is selected from any one of the following: zirconium oxychloride or its hydrate (such as ZrOCl 2· 8H2O), titanium n-butoxide, titanium n-propoxide, etc.

[0053] According to an embodiment of the present invention, the ligand is selected from any one of the following: benzoic acid, o-toluic acid, m-toluic acid, 5-chloro-thiophene-2-carboxylic acid, p-chlorobenzoic acid, p-fluorobenzoic acid, m-trifluoromethylbenzoic acid, and the like and derivatives thereof.

[0054] According to an embodiment of the present invention, the solvothermal synthesis method is to carry out a heating reaction in a solvent.

[0055] According to an embodiment of the present invention, the solvent is selected from alcohols, phenols, nitriles, mixed alcohols, mixed alcohol-phenols, and mixed alcohol-nitrile solvents.

[0056] According to an embodiment of the present invention, the alcohol solvent is C 1-20 Alcohol (such as C 1-10 Alcohol, C 1-6The alcohol solvent is preferably any one of methanol, ethanol, n-propanol, isopropanol, n-butanol, isobutanol, tert-butanol, n-pentanol, isopentanol, neopentyl alcohol, hexanol, heptanol, octanol, decanol, or any mixture thereof in any ratio. The alcohol solvent is preferably methanol, ethanol, n-propanol, isopropanol, or n-butanol.

[0057] According to an embodiment of the present invention, the nitrile solvent is preferably acetonitrile.

[0058] According to an embodiment of the present invention, the molar ratio of the zirconium source, the tin source and the ligand is (0.1-0.6):(0.2-0.9):1, for example (0.2-0.4):(0.3-0.6):1.

[0059] According to an embodiment of the present invention, the solvent is selected from a mixture of methanol and n-butanol, or isopropanol, or acetonitrile.

[0060] According to an embodiment of the present invention, the temperature of the solvothermal reaction may be 40 to 200°C, preferably 60 to 120°C.

[0061] According to an embodiment of the present invention, the solvent thermal reaction time may be 1 to 14 days, preferably 3 to 7 days.

[0062] According to an embodiment of the present invention, the reaction can be carried out in a sealed glass bottle or a polytetrafluoroethylene pressure reactor.

[0063] According to an embodiment of the present invention, the preparation method further comprises a step of purifying the product.

[0064] According to an embodiment of the present invention, the purification step includes: washing, separating and drying the reaction product at room temperature.

[0065] According to an embodiment of the present invention, an alcohol solvent is used in the washing step, and the alcohol solvent used for washing may be the same as or different from the alcohol added in the reaction.

[0066] The present invention also provides a patterned composition, which comprises the patterned material.

[0067] According to an embodiment of the present invention, the patterning composition further includes any one or more of a solvent, a stabilizer, a photosensitizer, and the like.

[0068] The present invention also provides a patterning method, comprising the following steps:

[0069] 1) dissolving the patterned material in a solvent, filtering, and attaching it to a substrate (by spin coating or other methods) to form a patterned coating;

[0070] 2) exposing the patterned coating to radiation;

[0071] 3) The exposed coating is brought into contact with a developer to form a pattern of the coating material.

[0072] According to an embodiment of the present invention, the substrate may be a hydrophilic or hydrophobic surface, such as a silicon wafer.

[0073] According to an embodiment of the present invention, the solvent is a solvent that can dissolve the above-mentioned patterned material; preferably, it includes but is not limited to any one of carboxylic acid esters, alcohols with 1-20 carbon atoms, halogenated hydrocarbons, aromatic hydrocarbons, amides, ketones, water and other solvents, or a mixture in any proportion thereof; further preferably, it is at least one of propylene glycol methyl ether acetate, ethyl lactate, isoacetate, methanol, isopropanol, heptanol, 2-heptanone, N,N-dimethylformamide, and water.

[0074] According to an embodiment of the present invention, examples of the carboxylates include but are not limited to: carboxylic acid ether esters such as propylene glycol methyl ether formate, ethylene glycol ethyl ether formate, propylene glycol ethyl ether formate, ethylene glycol methyl ether acetate, propylene glycol methyl ether acetate, etc.; carboxylic acid alkane esters such as ethyl formate, ethyl acetate, n-butyl acetate, ethyl lactate, n-propyl lactate, isopropyl lactate, etc.

[0075] According to an embodiment of the present invention, examples of alcohols having 1 to 20 carbon atoms include methanol, ethanol, isopropanol, n-butanol, cyclohexanol, heptanol, and the like.

[0076] According to an embodiment of the present invention, examples of the halogenated hydrocarbons include but are not limited to: dichloromethane, chloroform, and the like.

[0077] According to an embodiment of the present invention, examples of the aromatic hydrocarbons include, but are not limited to, benzene, toluene, xylene, and the like.

[0078] According to an embodiment of the present invention, examples of the amides include, but are not limited to, N,N-dimethylformamide, N,N-dimethylacetamide, and the like.

[0079] According to an embodiment of the present invention, examples of ketones include, but are not limited to, acetone, heptanone, and the like.

[0080] According to an embodiment of the present invention, the concentration of the patterning material in the solvent is 5 mg / mL to 30 mg / mL.

[0081] According to an embodiment of the present invention, after the patterned material is exposed to radiation, the solubility of the exposed and unexposed coating areas in the developer is greatly different. The patterned material contains metal ions with radiation-sensitive ligands before irradiation, and the radiation changes the properties of the coating material, thereby producing structures with different dissolution rates.

[0082] According to an embodiment of the present invention, the radiation is selected from electron beam, ultraviolet light, deep ultraviolet light, extreme ultraviolet light or a light source with a shorter wavelength.

[0083] According to an embodiment of the present invention, the developer is selected from any one of the following solvents or a mixture of any proportions of multiple solvents: a 0.5% to 20% aqueous solution of tetramethylammonium hydroxide (TMAH), heptanone, methanol, isopropanol, heptanol, N,N-dimethylformamide, propylene glycol methyl ether acetate, ethyl lactate, water, benzene, toluene, dichloromethane, etc.

[0084] According to an embodiment of the present invention, the developer is a solvent that can cause different dissolution rates of the material before and after irradiation.

[0085] According to an embodiment of the present invention, the developer is in contact with the patterned coating for no more than 10 minutes, for example, the development time is 5 to 240 seconds.

[0086] The present invention also provides the use of the above-mentioned patterned material or patterned composition in the preparation of photoresists; preferably electron beam photoresists, UV photoresists, DUV photoresists, EUV photoresists and other photoresists.

[0087] Beneficial Effects

[0088] The present invention provides a type of organic-inorganic hybrid metal oxide cluster patterning material, wherein the structure of the patterning material contains an octahedral [Zr6O8] building unit, which is connected to four butyltins through a cross-linked ligand and formed by adding a halogen group as a terminal ligand. The cross-linked ligand is a carboxylic acid ligand and an alkoxy ligand. The patterning material provided by the present invention can form a pattern with a resolution of 100 nm or even 50 nm after dissolution, filtration, spin coating, exposure and development.

[0089] The patterned material of the present invention contains adjustable cross-linked ligands, different radiation-responsive metals and terminal ligands. By introducing functional groups into the ligands, adjusting the types and proportions of different metals, and regulating the types and quantities of terminal ligands, its solubility, film-forming properties, light absorption capacity, photosensitivity, line edge roughness, and resolution can be further enhanced, thereby regulating the photolithographic performance of the patterned material. BRIEF DESCRIPTION OF THE DRAWINGS

[0090] Figure 1 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA) 10 Schematic diagram of the structure.

[0091] Figure 2 for(n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-oCH3) 10 Schematic diagram of the structure

[0092] Figure 3 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCH3) 10 Schematic diagram of the structure

[0093] Figure 4 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(TA-Cl) 10 Schematic diagram of the structure.

[0094] Figure 5 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pCl) 10 Schematic diagram of the structure.

[0095] Figure 6 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pF) 10 Schematic diagram of the structure.

[0096] Figure 7 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCF3) 10 Schematic diagram of the structure.

[0097] Figure 8 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA) 10 Infrared spectrum of .

[0098] Fig. 9 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-oCH3) 10 Infrared spectrum of .

[0099] Fig.10 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCH3) 10 Infrared spectrum of .

[0100] Fig.11 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(TA-Cl) 10 Infrared spectrum of .

[0101] Fig.12 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pCl) 10 Infrared spectrum of .

[0102] Fig.13 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pF) 10 Infrared spectrum of .

[0103] Fig.14 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCF3) 10 Infrared spectrum of .

[0104] Fig.15 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA) 10 Energy dispersive X-ray spectroscopy (EDX).

[0105] Fig.16 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-oCH3) 10 Energy dispersive X-ray spectroscopy (EDX).

[0106] Fig.17 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCH3) 10 Energy dispersive X-ray spectroscopy (EDX).

[0107] Fig.18 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(TA-Cl) 10 Energy dispersive X-ray spectroscopy (EDX).

[0108] Fig.19 for(n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pCl) 10 Energy dispersive X-ray spectroscopy (EDX).

[0109] Fig. 20 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pF) 10 Energy dispersive X-ray spectroscopy (EDX).

[0110] Fig.21 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCF3) 10 Energy dispersive X-ray spectroscopy (EDX).

[0111] Fig. 22 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pCl) 10 Materials at 100μC / cm 2 After patterning by exposure and development at a certain dose, SEM analysis showed that the width of the exposed line was 50 nm.

[0112] Fig.23 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pF) 10 Materials at 400μC / cm 2 After patterning by exposure and development at a certain dose, SEM analysis showed that the width of the exposed line was 50 nm.

[0113] Fig.24 for( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCF3) 10 Materials at 50μC / cm 2 After patterning by exposure and development at a certain dose, SEM analysis showed that the width of the exposed line was 50 nm.

[0114] BA represents benzoate, with the molecular formula C7H5O2; BA-oCH3 represents o-methylbenzoate, with the molecular formula C8H7O2; BA-mCH3 represents m-methylbenzoate, with the molecular formula C8H7O2; TA-Cl represents 5-chloro-thiophene-2-carboxylate, with the molecular formula C5H2O2SCl; BA-pCl represents p-chlorobenzoate, with the molecular formula C7H4O2Cl; BA-pF represents p-fluorobenzoate, with the molecular formula C7H4O2F; BA-mCF3 represents m-trifluoromethylbenzoate, with the molecular formula C8H4O2F3.

[0115] In order to make the structure clearer, some oxygen, carbon, nitrogen, hydrogen and other atoms are omitted in the schematic diagram. DETAILED DESCRIPTION

[0116] The technical scheme of the present invention will be further described in detail below in conjunction with specific embodiments. It should be understood that the following embodiments are only exemplary descriptions and explanations of the present invention and should not be construed as limiting the scope of protection of the present invention. All technologies implemented based on the above content of the present invention are included in the scope that the present invention is intended to protect.

[0117] Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available or can be prepared by known methods.

[0118] Example 1 Preparation and characterization of mixed organic-inorganic hybrid metal oxide cluster patterned materials

[0119] 1.( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA) 10 (BA stands for benzoate, with the molecular formula C7H5O2)

[0120] In a 20 mL glass reaction bottle, ZrOCl 2· 8H2O (0.31mmol, 100mg), butyl stannoic acid (0.48mmol, 100mg), benzoic acid (1mmol, 122mg) were mixed with methanol (1.5mL) and n-butanol (1.5mL), the lid was tightened, and the mixture was heated to 80°C. After 5 days, the mixture was cooled to room temperature, and crystals precipitated. The yield was 25%. The crystals were separated and rinsed with methanol.

[0121] Referring to the above steps, the reaction temperature is adjusted to 60-100° C., the reaction time is 3-7 days, and the yield is 20%-30%.

[0122] The crystallographic data are as follows: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is c is α is 73.9040(10)°, β is 85.4470(10)°, γ is 68.1800(10)°, and V is

[0123] 2.( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-oCH3) 10 (BA-oCH3 represents o-methylbenzoate, with the molecular formula C8H7O2)

[0124] In a 20 mL glass reaction bottle, ZrOCl 2· 8H2O (0.31mmol, 100mg), butyl stannoic acid (0.48mmol, 100mg), o-methyl benzoic acid (1mmol, 136mg) were mixed with methanol (2.5mL) and ethanol (2.5mL), the lid was tightened, and the mixture was heated to 80°C. After 5 days, the mixture was cooled to room temperature and crystals were precipitated. The yield was 30%. The crystals were separated and rinsed with methanol.

[0125] Referring to the above steps, the reaction temperature is adjusted to 60-100° C., the reaction time is 3-7 days, and the yield is 20%-30%.

[0126] The crystallographic data are as follows: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is 19.56 c is α is 97.3350(10)°, β is 90.0890(10)°, γ is 110.0550(10)°, and V is

[0127] 3.( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCH3) 10 (BA-mCH3 represents m-methylbenzoate, with the molecular formula C8H7O2)

[0128] In a 20 mL glass reaction bottle, ZrOCl 2· 8H2O (0.31mmol, 100mg), butyl stannoic acid (0.48mmol, 100mg), m-methyl benzoic acid (1mmol, 136mg) were mixed with methanol (2.5mL) and acetonitrile (2.5mL), the lid was tightened, and the mixture was heated to 80°C. After 5 days, the mixture was cooled to room temperature, and crystals precipitated. The yield was 25%. The crystals were separated and rinsed with methanol.

[0129] Referring to the above steps, the reaction temperature is adjusted to 60-100° C., the reaction time is 3-7 days, and the yield is 20%-30%.

[0130] The crystallographic data are: the crystal system is monoclinic, the space group is C2 / c, and the unit cell parameter a is b is c is α is 90°, β is 96.103(4)°, γ is 90°, and V is

[0131] 4.( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(TA-Cl) 10 (TA-Cl represents 5-chloro-thiophene-2-carboxylate, molecular formula is C5H2O2SCl)

[0132] In a 20 mL glass reaction bottle, ZrOCl 2· 8H2O (0.31mmol, 100mg), butyl stannoic acid (0.48mmol, 100mg), 5-chloro-thiophene-2-carboxylic acid (0.62mmol, 100mg) were mixed with methanol (2.5mL) and n-propanol (2.5mL), the lid was tightened, and the mixture was heated to 80°C. After 5 days, the mixture was cooled to room temperature, and crystals precipitated. The yield was 30%. The crystals were separated and rinsed with methanol.

[0133] Referring to the above steps, the reaction temperature is adjusted to 60-100° C., the reaction time is 3-7 days, and the yield is 20%-30%.

[0134] The crystallographic data are: the crystal system is monoclinic, the space group is I2 / a, and the unit cell parameter a is b is c is α is 90.0°, β is 104.977(2)°, γ is 90.0°, and V is

[0135] 5.( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pCl) 10 (BA-pCl represents p-chlorobenzoate, with the molecular formula C7H4O2Cl)

[0136] In a 20 mL glass reaction bottle, ZrOCl 2·8H2O (0.31mmol, 100mg), butyl stannoic acid (0.48mmol, 100mg), p-chlorobenzoic acid (1mmol, 156mg) were mixed with methanol (2mL) and isopropanol (3mL), the lid was tightened, and the mixture was heated to 80°C. After 5 days, the mixture was cooled to room temperature and crystals precipitated. The yield was 25%. The crystals were separated and rinsed with methanol.

[0137] Referring to the above steps, the reaction temperature is adjusted to 60-100° C., the reaction time is 3-7 days, and the yield is 20%-30%.

[0138] The crystallographic data are as follows: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is c is α is 75.081(2)°, β is 72.591(2)°, γ is 85.302(2)°, and V is

[0139] 6.( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pF) 10 (BA-pF stands for para-fluorobenzoate, with the molecular formula C7H4O2F)

[0140] In a 20 mL glass reaction bottle, ZrOCl 2· 8H2O (0.31mmol, 100mg), butyl stannoic acid (0.48mmol, 100mg), p-fluorobenzoic acid (1mmol, 140mg) were mixed with methanol (4mL) and acetonitrile (1mL), the lid was tightened, and the mixture was heated to 80°C. After 5 days, the mixture was cooled to room temperature and crystals were precipitated. The yield was 30%. The crystals were separated and rinsed with methanol.

[0141] Referring to the above steps, the reaction temperature is adjusted to 60-100° C., the reaction time is 3-7 days, and the yield is 20%-30%.

[0142] The crystallographic data are as follows: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is 17.35 c is α is β is 74.8997(17)°, γ is 86.2910(18)°, V is 56

[0143]

[0144] 7.( nBuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCF3) 10 (BA-mCF3 represents m-trifluoromethylbenzoate, molecular formula C8H4O2F3)

[0145] In a 20 mL glass reaction bottle, ZrOCl 2· 8H2O (0.31mmol, 100mg), butyl stannoic acid (0.48mmol, 100mg), m-trifluoromethyl benzoic acid (0.53mmol, 100mg) were mixed with methanol (4mL) and acetonitrile (1mL), the lid was tightened, and the mixture was heated to 80°C. After 5 days, the mixture was cooled to room temperature, and crystals precipitated. The yield was 15%. The crystals were separated and rinsed with methanol.

[0146] Referring to the above steps, the reaction temperature is adjusted to 60-100° C., the reaction time is 3-7 days, and the yield is 10%-20%.

[0147] The crystallographic data are: the crystal system is monoclinic, the space group is C2 / c, and the unit cell parameter a is b is c is α is 90°, β is 93.136(2)°, γ is 90°, and V is

[0148] The above compound (RSn)4Zr6X2(μ-O)8(μ-R'O)8(L) 10 The structural diagram is as follows Figure 1-7 As shown, the infrared spectrum is Figure 8-14 As shown, the energy dispersive X-ray spectrum (EDX) is as follows Figure 15-21 shown.

[0149] Analysis shows that the structural characteristics of the above four mixed-type organic metal oxide cluster patterning materials are:

[0150] 1) There is an octahedral [Zr6O8] building unit, which is connected to four butyltin groups through a cross-linked ligand, and a halogen group and a carboxylic acid ligand are added as terminal ligands. The cross-linked ligands are carboxylic acid ligands and alkoxy ligands.

[0151] (like Figure 1-7 shown).

[0152] 2) There are easily substituted carboxylic acid, alkoxy, halogen cross-linked or terminal ligands, so the active site can introduce functional organic ligands, radiation-sensitive groups, etc. to enhance its solubility, film-forming properties, light absorption ability, photosensitivity, improve line edge roughness and resolution, and regulate the lithography performance of patterned materials.

[0153] Example 2

[0154] 1. Silicon wafer processing

[0155] Clean the silicon wafer in an acidic or alkaline solution for 15 to 30 minutes, then wash it with deionized water and then with isopropyl alcohol. Use an air gun to blow dry the surface liquid before use.

[0156] 2. Film preparation

[0157] 10 mg of the mixed organometallic oxygen cluster patterning material prepared in Example 1 was dissolved in 1 mL of propylene glycol methyl ether acetate solvent, and the solution was filtered. An appropriate amount of the filtered solution was transferred to form a coating on the surface of the treated silicon substrate by spin coating.

[0158] Referring to the above steps, 5-30 mg of the mixed organometallic oxygen cluster patterning material prepared in Example 1 was dissolved in 1 mL of propylene glycol methyl ether acetate solvent, and the solution was filtered. An appropriate amount of the filtered solution was transferred to form a coating on the surface of the treated silicon substrate by spin coating.

[0159] 3. Exposure

[0160] After the electron beam selectively irradiates the patterned material film layer, the irradiated part undergoes chemical changes and the solubility changes. That is, the solubility of the exposed and unexposed film layer areas in the developer is greatly different, thus forming a pattern.

[0161] 4. Development

[0162] During the development process, a developer is used to contact the exposed film layer to dissolve and remove part of the patterned material film layer. The dissolved part is the exposed film layer or the unexposed film layer.

[0163] The developer used is a mixture of N,N-dimethylformamide or isopropyl alcohol and water (volume ratio range is 10:1 to 1:10). The developing time is 5s to 120s.

[0164] 5. Pattern Characterization

[0165] The pattern of the coating material after exposure and development was characterized by a scanning electron microscope (SEM). The results are as follows: Figure 22-24 shown.

[0166] The resolution of the pattern formed by the mixed organometallic oxygen cluster patterning material compounds 5-7 in Example 1 after dissolution, filtration, spin coating, exposure and development can reach 100 nm, or even 50 nm.

[0167] The above is an explanation of the embodiments of the present invention. However, the present invention is not limited to the above embodiments. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A patterned material, characterized in that: Its molecular formula is shown in formula (I): (RSn)4Zr6X2(μ-O)8(μ-R'O)8(L) 10 Formula (I); Wherein, R is selected from H, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl or C 6-20 Aryl; R' is selected from H, C 1-20 Alkyl, C 2-20 Alkenyl, C 2-20 Alkynyl or C 6-20 Aryl; X contains the same or different ligands, which are independently selected from ligands capable of coordinating with Zr and Sn; L contains the same or different ligands, which are independently selected from ligands capable of coordinating with Zr and Sn.

2. The patterned material according to claim 1, characterized in that R is selected from H, C 1-10 Alkyl, C 2-10 Alkenyl, C 2-10 Alkynyl or C 6-10 Aryl; Preferably, R is selected from H, C 1-6 Alkyl, C 2-6 Alkenyl, C 2-6 Alkynyl or C 6-10 Aryl. Preferably, R is selected from H, C 1-4 Alkyl, C 2-4 Alkenyl, C 2-4 Alkynyl or C 6-10 Aryl. Preferably, R is selected from H, methyl, ethyl, propyl, n-butyl, vinyl, methylpropenyl, propenyl, butenyl, ethynyl, propynyl, butynyl, phenyl, naphthyl. Preferably, R' is selected from H, C 1-10 Alkyl, C 2-10 Alkenyl, C 2-10 Alkynyl or C 6-10 Aryl; Preferably, R' is selected from H, C 1-6 Alkyl, C 2-6 Alkenyl, C 2-6 Alkynyl or C 6-10 Aryl. Preferably, R' is selected from H, C 1-4 Alkyl, C 2-4 Alkenyl, C 2-4 Alkynyl or C 6-10 Aryl. Preferably, R' is selected from H, methyl, ethyl, propyl, butyl, vinyl, methacryl, propenyl, butenyl, ethynyl, propynyl, butynyl, phenyl, naphthyl. Preferably, X comprises the same or different ligands, independently selected from ligands containing but not limited to C, O, S, Se, Te, N, P, As, Sb, Cl, Br, I, etc. as coordinating atoms. Preferably, L comprises identical or different ligands, independently selected from ligands containing but not limited to C, O, S, Se, Te, N, P, As, Sb, Cl, Br, I, etc. as coordinating atoms.

3. The patterned material according to claim 1 or 2, characterized in that: L comprises the same or different ligands, independently selected from halogens, alkanes (C 1-20 Alkyl), aromatic hydrocarbons (C 6-20 Aromatic hydrocarbons), olefins (C 2-20 alkenyl), alkynes (C 2-20 alkynyl), carboxylic acids (e.g., carboxylic acids or derivatives thereof, such as benzoate, o-methylbenzoate, m-methylbenzoate, 5-chloro-thiophene-2-carboxylate, p-chlorobenzoate, p-fluorobenzoate or trifluoromethylbenzoate), alcohols, thiols, phenols, sulfonic acids, phosphoric / phosphonic acids, phosphines, arsenic acids, nitriles, alcoholamines, pyridines, pyrazoles, imidazoles, piperazines, pyrazines, H2O, SO4, NO3 or ligands such as the above ions; Preferably, L comprises identical or different ligands, and the different ligands may be present in any ratio. Preferably, part or all of the Zr and Sn ions can be replaced by other elements, such as radiation-sensitive elements. Preferably, the radiation-sensitive elements are selected from any one of Na, Mg, Al, K, Ca, Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zn, Ga, Ge, As, Rb, Sr, Y, Zr, Nb, Mo, Tc, Ru, Rh, Pd, Ag, Cd, In, Sn, Sb, Te, Cs, Ba, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, Lu, Hf, Ta, W, Re, Os, Ir, Pt, Au, Hg, Pb, Bi, Po, or a combination thereof. Preferably, functional groups can be further introduced into R, R', X, and L. The introduction of functional groups can adjust the light absorption ability, solubility, film-forming properties and other properties of the patterned material, thereby affecting the film thickness, film roughness, resolution, film adhesion and corrosion resistance. Preferably, a radiation sensitive functional group may be further introduced into R, R', X, and L. The introduction of the radiation sensitive functional group can enhance the photosensitivity of the patterned material, improve the line edge roughness, and increase the resolution. The radiation sensitive functional group is, for example, a double bond, a triple bond, propylene oxide, or a compound of a combination thereof. Preferably, the ratio of the coordinating atoms of the ligands to the metal ions in the patterning material can be adjusted to improve its sensitivity, line edge roughness and resolution. Preferably, the patterned material has an octahedral [Zr6O8] building unit, which is connected to four butyltin groups through a cross-linked ligand and is formed by adding a halogen group and a carboxylic acid ligand as a terminal ligand; the cross-linked ligand is a carboxylic acid ligand and an alkoxy ligand.

4. The patterned material according to any one of claims 1 to 3, characterized in that: The patterning material is selected from the following compounds 1 to 7: Compound 1: ( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA) 10 ; Compound 2: ( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-oCH3) 10 ; Compound 3: ( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCH3) 10 ; Compound 4: ( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(TA-Cl) 10 ; Compound 5: ( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pCl) 10 ; Compound 6: ( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-pF) 10 ; Compound 7: ( n BuSn)4Zr6Cl2(μ3-O)4(μ4-O)4(μ-MeO)8(BA-mCF3) 10 ; Among them, BA represents benzoate, with the molecular formula of C7H5O2; BA-oCH3 represents o-methylbenzoate, with the molecular formula of C8H7O2; BA-mCH3 represents m-methylbenzoate, with the molecular formula of C8H7O2; TA-Cl represents 5-chloro-thiophene-2-carboxylate, with the molecular formula of C5H2O2SCl; BA-pCl represents p-chlorobenzoate, with the molecular formula of C7H4O2Cl; BA-pF represents p-fluorobenzoate, with the molecular formula of C7H4O2F; BA-mCF3 represents m-trifluoromethylbenzoate, with the molecular formula of C8H4O2F3.

5. The patterned material according to claim 4, characterized in that The crystal parameters of compound 1 are: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is c is α is 73.9040(10)°, β is 85.4470(10)°, γ is 68.1800(10)°, and V is Preferably, the crystal parameters of compound 2 are: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is c is α is 97.3350(10)°, β is 90.0890(10)°, γ is 110.0550(10)°, and V is Preferably, the crystal parameters of compound 3 are: the crystal system is monoclinic, the space group is C2 / c, and the unit cell parameter a is b is c is α is 90°, β is 96.103(4)°, γ is 90°, and V is Preferably, the crystal parameters of compound 4 are: the crystal system is monoclinic, the space group is I2 / a, and the unit cell parameter a is b is c is α is 90.0°, β is 104.977(2)°, γ is 90.0°, and V is Preferably, the crystal parameters of compound 5 are: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is c is α is 75.081(2)°, β is 72.591(2)°, γ is 85.302(2)°, and V is Preferably, the crystal parameters of compound 6 are: the crystal system is triclinic, the space group is P-1, and the unit cell parameter a is b is c is α is 77.8622(12)°, β is 74.8997(17)°, γ is 86.2910(18)°, and V is Preferably, the crystal parameters of compound 7 are: the crystal system is monoclinic, the space group is C2 / c, and the unit cell parameter a is b is c is α is 90°, β is 93.136(2)°, γ is 90°, and V is 6. The method for preparing a patterned material according to any one of claims 1 to 5, characterized in that: The following steps are involved: The material can be prepared by a solvothermal synthesis method using a tin source, a zirconium source, a ligand and a solvent; 7. The preparation method according to claim 6, characterized in that: The tin source is selected from any one of the following: butyl stannoic acid, dibutyl tin chloride, dibutyl stannoic acid, phenyl tin chloride; The zirconium source is selected from any one of the following: zirconium oxychloride or its hydrate, titanium n-butoxide, titanium n-propoxide; The ligand is selected from any one of the following: benzoic acid, o-toluic acid, m-toluic acid, 5-chloro-thiophene-2-carboxylic acid, p-chlorobenzoic acid, p-fluorobenzoic acid, m-trifluoromethylbenzoic acid and derivatives thereof.

8. A patterned composition, characterized in that The patterning composition comprises the patterning material according to any one of claims 1 to 5.

9. A patterning method, characterized in that: The following steps are involved: 1) dissolving the patterned material according to any one of claims 1 to 5 in a solvent, filtering, and attaching the patterned material to a substrate to form a patterned coating; 2) exposing the patterned coating to radiation; 3) The exposed coating is brought into contact with a developer to form a pattern of the coating material.

10. Use of the patterning material according to any one of claims 1 to 5 in preparing a photoresist; The photoresist is electron beam photoresist, UV photoresist, DUV photoresist or EUV photoresist.